IL-13 mRNA Tissue Content Identifies Two Subsets of Adult Ulcerative Colitis Patients With Different Clinical and Mucosa-Associated Microbiota Profiles. (10th September 2019) - Butera, Alessia; Di Paola, Monica; Vitali, Francesco; De Nitto, Daniela; Covotta, Francesco; Borrini, Francesco; Pica, Roberta; De Filippo, Carlotta; Cavalieri, Duccio; Giuliani, Alessandro; Pronio, Annamaria; Boirivant, Monica
Abstract: Background and Aims: A personalized approach to therapy hold great promise to improve disease outcomes. To this end, the identification of different subsets of patients according to the prevalent pathogenic process might guide the choice of therapeutic strategy. We hypothesize that ulcerative colitis [UC] patients might be stratified according to distinctive cytokine profiles and/or to a specific mucosa-associated microbiota. Methods: In a cohort of clinically and endoscopic active UC patients and controls, we used quantitative PCR to analyse the mucosal cytokine mRNA content and 16S rRNA gene sequencing to assess the mucosa-associated microbiota composition. Results: We demonstrate, by means of data-driven approach, the existence of a specific UC patient subgroup characterized by elevated IL-13 mRNA tissue content separate from patients with low IL-13 mRNA tissue content. The two subsets differ in clinical–pathological characteristics. High IL-13 mRNA patients are younger at diagnosis and have a higher prevalence of extensive colitis than low IL-13 mRNA patients. They also show more frequent use of steroid/immunosuppressant/anti-tumour necrosis factor α therapy during 1 year of follow-up. The two subgroups show differential enrichment of mucosa-associated microbiota genera with a prevalence of Prevotella in patients with high IL-13 mRNA tissue content and Sutterella and Acidaminococcus in patients with low IL-13 mRNA tissue content. Conclusion: Assessment of mucosal IL-13 mRNA might help in the identification of a patient subgroup that might benefit from a therapeutic approach modulating IL-13. Podcast: This article has an associated podcast which can be accessed at https://academic.oup.com/ecco-jcc/pages/podcast